The Long‐Term Effects of Cancer Treatment on Sexuality and Couple Relationships. Issue 3 (8th October 2020) - Di Mattei, Valentina Elisabetta; Perego, Gaia; Taranto, Paola; Mazzetti, Martina; Marotta, Elena; Candiani, Massimo; Salvatore, Stefano
Abstract : Breast cancer and its pharmacological treatment often induce an impairment in women's sexual functioning and couple relationships, as a consequence of physiological changes and psychosocial issues that may arise and persist long after treatment. This study aims to evaluate the sexual functioning, the quality of the couple relationship, and the overall health status of breast cancer survivors. A further objective is to determine the predictive role of specific clinical and sociodemographic variables for sexual functioning and the couple relationship. Sixty‐four breast cancer survivors completed the following questionnaires: the Female Sexual Function Index (FSFI), the Dyadic Adjustment Scale (DAS), the Short Form Health Survey ‐12 (SF‐12), and a self‐report questionnaire to collect sociodemographic characteristics. Clinical information was retrieved from medical records. Compared to normative data, our sample reported significantly ( p < .01) lower mean scores in the FSFI, DAS, and Physical Component (PCS) and Mental Component Summary (MCS) of the SF‐12. Multiple regression analyses show a significant effect of age, hormonal therapy, and psychological well‐being on sexual functioning and a significant effect of physical and mental well‐being on the quality of the couple relationship. Additionally, 75% of patients qualified for sexual dysfunction as measured by the FSFI global scale, and 71.9% declared they were not adequately informed about the side effects of treatments on sexuality. The high prevalence of sexual dysfunction in breast cancer survivors underlines the need for specific attention to this problem, starting from a complete and targeted communication between patients and health providers regarding these side effects. RESUMEN: El cáncer de mama y su tratamiento farmacológico frecuentemente producen un deterioro del funcionamiento sexual de las mujeres y de las relaciones de pareja como consecuencia de los cambios fisiológicos y los problemas psicosociales que pueden surgir y continuar mucho después del tratamiento. Este estudio tiene como finalidad evaluar el funcionamiento sexual, la calidad de la relación de pareja y el estado de salud general de las sobrevivientes de cáncer de mama. Otro objetivo es determinar el papel predictivo que desempeñan las variables clínicas y sociodemográficas específicas para el funcionamiento sexual y la relación de pareja. Sesenta y cuatro sobrevivientes de cáncer de mama contestaron los siguientes cuestionarios: el Índice de la Función Sexual Femenina ( Female Sexual Function Index, FSFI), la Escala de Ajuste Diádico ( Dyadic Adjustment Scale, DAS), la Encuesta Breve sobre la Salud‐12 ( Short Form Health Survey‐12, SF‐12) y un cuestionario de autoinforme para recopilar características sociodemográficas. Se obtuvo información clínica de expedientes médicos. En comparación con los datos normativos, nuestra muestra informó puntajes de la media significativamente más bajos (p<0.01) en el FSFI, en la DAS y en el Resumen del Componente Físico (PCS) y del Componente Mental (MCS) de la SF‐12. Los análisis de regresión múltiple indican un efecto significativo de la edad, la terapia hormonal y el bienestar psicológico en el funcionamiento sexual, y un efecto significativo del bienestar físico y mental en la calidad de la relación de pareja. Además, el 75 % de las pacientes reunió los requisitos de disfunción sexual según la medición de la escala global del FSFI, y el 71.9 % declaró que no estaba adecuadamente informado acerca de los efectos secundarios de los tratamientos en la sexualidad. La alta prevalencia de disfunción sexual en las sobrevivientes de cáncer de mama subraya la necesidad de atender este problema de manera específica, partiendo de una comunicación completa y dirigida entre pacientes y profesionales de la salud con respecto a estos efectos secundarios. 摘要: 乳腺癌及其药物治疗往往会对妇女的性功能和夫妻关系造成损害，这是由生理变化和社会心理问题引起的，并在治疗后长期存在。本研究旨在评估乳腺癌幸存者的性功能、夫妻关系的质量和整体健康状况。另一个目标是确定特定临床和社会人口学变量对性功能和夫妻关系的预测作用。 对64名乳腺癌幸存者进行调查。他们完成了以下问卷：女性性功能指数(FSFI)、二元调整量表(DAS)、健康调查简表‐12(SF‐12)，以及一份收集社会人口特征的自我报告问卷。临床资料则从病历中提取。 与常模数据相比，我们的样本报告的FSFI、DAS、SF‐12的生理成分（PCS）和心理成分总结（MCS）的平均得分显著降低（P<0.01）。多元回归分析显示，年龄、激素治疗和心理健康对性功能有显著影响，身心健康对夫妻关系质量有显著影响。此外，75%的患者符合FSFI全局量表测量的性功能障碍，71.9%的患者宣称没有充分了解乳腺癌治疗对性欲方面的副作用。性功能障碍的发病率高。乳腺癌幸存者中性功能障碍的高发率凸显了对这一问题给予特别关注的必要性，从患者和医疗服务提供者之间就这些副作用进行全面和有针对性的沟通开始。